Pengaruh Pengalaman Kerja, Disiplin Kerja, Dan Etika Kerja Islam Terhadap Kinerja Karyawan Pada CV. BG. Sukirman Kencong - M. Hamzah Bin Ali; Retno Endah Supeni; Rusdiyanto (Universitas Muhammadiyah Metro, 2024)
Managing human resources (HR) has become important in this century, considering that HRis central to achieving organizational goals. Without the role of humans, even though thevarious areas needed have been fulfilled, the organization will never run smoothly becausehumans are the driving force or lever that determines the running of the organization. Thetype of research used is quantitative research and data collection techniques usingquestionnaires, interviews and documentation for 150 respondents. The analytical tool usedin this research is multiple linear regression analysis. The test results show that workexperience and work discipline have a significant effect on employee performance CV. BG.Sukirman kencong, while Islamic work ethics do not have a significant effect on employeeperformance CV. BG. Sukirman Kencong. This research is only able to explain employeeperformance of 77.2%, so there are other factors outside the model studied that is able toexplain employee performance.